In vivo analysis of palm wine (Elaeis guineensis) volatile organic compounds (VOCs) by proton transfer reaction-mass spectrometry. - Olusegun , Lasekan; Otto, Sabine (Elsevier, 2009)
The in vivo volatile organic compounds (VOCs) release patterns in palm wine was carried out using the PTR-MS. In order to analyze the complex mixtures of VOCs in palm wine, the fragmentation patterns of 14 known aroma compounds of palm wine were also investigated. Results revealed masses m/z (43, 47, 61, 65, 75, 89 and 93) as the predominant ones measured in-breathe exhaled from the nose, during consumption of palm wine. Further studies of aroma's fragmentation patterns, showed that the m/z 43 is characteristic of fragment of various compounds, while m/z 47 is ethanol, m/z 61(acetic acid), m/z 65 (protonated ethanol cluster ions), m/z 75 (methyl acetate), m/z 89 (acetoin) and m/z 93 (2-phenylethanol) respectively. The dynamic release parameters (Imax and tmax) of the 7 masses revealed significant (P = 0.05) differences, between maximum intensity (Imax) and no significant (P = 0.05) differences between tmax among VOCs respectively.